Motivation of Small and Medium Scale Enterprises (SMEs) in Implementing Environmental Management Systems (EMS): With Special reference to Sri Lanka - Weerasiri , R.A. Sudath; Dissanayake , D.M.R. (Gyan Management Journal, 2011)
Small and Medium scale Enterprises are very important for a country's economy as they account for about 70% of Gross National Product (GNP), although this may be vary across different countries. On the other hand SM Es are reported as contributing up to 70% of all industrial pollution {11]. Therefore improving environmental performance of SM Es along with a constructive emphasis of Environmental Management Systems {EMS!>) is strategically important, irrespective of their sale of operation. The motivation towards implementation of EMSs in SMEs depend on regulatory complains, market requirements, stakeholders' pressure, cost reduction and enhance reputation. This study was framed to 45 SM Es in three sectors and the empirical findings said that motivation for implementation of EMSs in SMEs is almost dominated by individual motives provided entrepreneurial leadership styles than regulatory, social and market drivers. The overall impact of individual motives was in above averaged level as per the descriptive statistical analysis.
Keywords: Environmental Management Systems; Small and Medium scale Enterprises; ISO 14001; Motivation